Efficacy of Diving Reflex in Near-Term Fetal Tachycardia. Issue 2 (February 2021) - Papa, Marco; Mauri, Lucia; Sandrini, Camilla; Persico, Nicola; Colli, Anna Maria
Abstract : BACKGROUND: Sustained fetal supraventricular tachycardia is a potentially life-threatening disorder and is usually treated by administering antiarrhythmia drugs to the mother, which can require at least 48–72 hours to achieve normal sinus rhythm. In neonates with supraventricular tachycardia, first-line treatment is stimulation of the vagus nerve to elicit the diving reflex, commonly by application of a cold pack to the face, with a high, albeit sometimes temporary, success rate. CASE: We describe a case of fetal supraventricular tachycardia at term treated successfully by eliciting the diving reflex with an ice pack to the maternal abdomen over the lower uterine segment. The neonate was given propranolol augmented with flecainide because of recurrent supraventricular tachycardia. He remained in a stable sinus rhythm without side effects 5 months later. CONCLUSIONS: Cardioversion of fetal supraventricular tachycardia at term by eliciting the diving reflex could be offered to allow normal labor and vaginal delivery. Abstract : Cardioversion of fetal supraventricular tachycardia could be approached by eliciting the diving reflex before pharmacologic treatment or delivery, depending on gestational age and fetal status.